Program Manajemen Stress (Problem, Emotion, and Religious Coping ) dalam Meningkatkan Kesehatan Mental pada Lanjut Usia Berpenyakit Kronis - Suhermi S; Rahmawati Ramli (Idea Pengabdian Masyarakat, 2022)
The relatively long duration of chronic disease makes chronic disease vulnerable to affecting various aspects of the sufferer's life, both physical, psychological, and social aspects. This causes chronic disease sufferers usually also experience obstacles to carry out their daily activities. Stress management programs aim to reduce stress levels and improve mental and physical health in the elderly. By teaching several stress management techniques such as progressive muscle relaxation, breathing relaxation, prayer/remembrance, sharing, and doing fitness exercises. The implementation of stress management consists of seven sessions with a meeting duration of 2.5 – 3 hours, twice a week. In general, each session contains stress coping techniques and participants share their experiences with the techniques being discussed. However, in the second to last session, the meeting was also added by doing relaxation exercises before starting the session, both breathing relaxation, progressive muscle relaxation, prayer/remembrance and fitness exercises.